FAKTOR – FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA PADA PERUSAHAAN SEKTOR INFRASTRUKTUR YANG TERDAFTAR DI BEI - Dona Friski Sinulingga; Muhammad Fuad; Nasrul Kahfi Lubis (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2022)
This study aims to discuss the effect of Cash Flow Volatility, Accrual Size and Debt Level on Earnings Persistence in Infrastructure sector companies listed on the IDX for the period 2010 – 2019. The data used in this study uses secondary data obtained from the published financial statements of Infrastructure sector companies. . The data analysis method used was multiple linear regression and used statistical tools, namely SPSS (Statistical Package for the Social Science) software. The results show that Cash Flow Volatility has a positive but not significant effect on Earning Persistence, Accrual Size has a negative and significant effect on Earning Persistence, Debt Level has a negative and significant effect on Earning Persistence. And Cash Flow Volatility, Accrual Size and Debt Level simultaneously have a significant effect on Earning Persistence.